Sifat Fisis dan Mekanis Papan Partikel Hibrida dari Kayu Cepat Tumbuh dan Bambu dengan Perlakuan Perendaman Panas ( Physical and Mechanical Properties of Hybrid Particleboard from Fast Growing Wood Species and Bamboo with Heat Immersion Treatment) - Soleh Muhamad; Marwanto Marwanto; Muhammad I Maulana; Sena Maulana; Adesna Fatrawana; Wahyu Hidayat; Rita K Sari; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
The purpose of this study was to evaluate the physical and mechanical properties of hybrid particleboard made from combination of sengon wood (Falcataria moluccana), jabon wood (Anthocephalus cadamba), and betung bamboo (Dendrocalamus asper) with hot water immersion treatment. Pretreatment with hot water immersion was carried out in water bath at 80 ºC for 2 hours. The boards were made using urea formaldehyde (UF) adhesive with (30x30x0.9) cm3 size and 0.6 g cm-3 target density. Physical and mechanical properties of hybrid particleboards were evaluated based on JIS A 5908-2003 standard. The results showed that the combination treatment with bamboo particles can increase the mechanical properties and dimensional stability of the particleboards especially when combined with jabon particles. Hot water immersion treatment can improve the mechanical properties (MOE, MOR and IB) of hybrid particleboards. However, hot water immersion treatment decreased dimensional stability (thickness swelling and water absorption) of hybrid particleboards.